Analisis Industry's Competitiveness pada Crude Palm Oil Indonesia - Dian Widyaningtyas; Tri Widodo (JABE (Journal of Applied Business and Economic), 2016)
Indonesia’s palm oil industry has a comparative advantage in term of vast areas of land and the the cheapest palm oil production cost in the world. In this study we concern on the industry competitiveness of Indonesia’s crude palm oil (CPO). This study also discusses the opportunities of CPO’s industry in the future. Here, the industry competitiveness is analyzed using Porter's Five-Forces. Our result showed that there is strong pressure in almost all perspectives, except the input power of buyers and entry. This high pressure related to the amount of worldwide palm oil producers, the availability of soybean oil which indicated as the main competitor for the industry as alternative products, and the internal rivalry. Thus, we analyze the strength of the palm oil industry to find opportunities for further development. Some great opportunities might be applicable for developing the CPO industries are, e.g., optimalizing the use of palm oil as biofuels, maximizing the competitiveness of palm oil among other vegetable oils in terms of production capacity, and boosting the demand from europe as new importers.